The voice of the moldavian land - Maria Bieşu (Confluenţe Bibliologice, 2020)
The author writes about the exhibition dedicated to National Opera Prima Donna, the international soprano Maria Bieşu on the occasion of her 85th birthday. The exhibition includes documents from the collection of the USARB Scientiﬁc Library: works in diﬀerent editions, audiovisual documents, critical monographs in Romanian and Russian, articles from periodicals, duets and collaborations, appearances in reference sources. The exhibition is accompanied by a bibliography of traditional and electronic resources.
Keywords: online exhibition; Maria Bieşu (1935-2012); collection of the USARB Scientiﬁc Library; Bessarabian interpreters